Ventrikel Kiri dengan Jalan Masuk dan Keluar Ganda, Trasnposisi Arteri Besar, Duktus Arteriosus Paten Defek Septum Ventricle Inlet - Sylvie Sakasasmita; Ganesja M. Harimurti; Dicky Fakhri; Venty Venty (The Indonesian Heart Association, 2016)
Congenital heart disease is an interesting area which present a great various arrangement of the cardiac stucture. We present a rare case of 11 months old male with complex congenital heart disease consisted of Double Inlet Left Ventricle (DILV), Double Outlet Left Ventricle (DOLV) with Malposition of Great Arteries, Inlet Ventricle Septal Defect (VSD) and Patent Ductus Arteriosus (PDA).Patient was an eleven months old male who was admitted in our institution for cardiac operation. He was diagnosed with congenital heart disease since three days old with initial presentation of cyanosis when he was crying. His physical growth was retarded but his developmental Milestones was considered normal. On admission, his oxygen saturation was 88% with ambient air. The diagnosis was confirmed by echocardiography. He was planned to undergo staging surgery which would end to Fontan Procedure. Pulmonary Artery (PA) banding was performed to reduce blood flow to pulmonary circulation, distribute more blood from the left ventricle to aorta and systemic circulation and prepare for bidirectional Glenn Shunt procedure one year later and Fontan procedure a year after that.